2014
DOI: 10.1002/ijc.29142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the exercise‐inducible myokine irisin on malignant and non‐malignant breast epithelial cell behavior in vitro

Abstract: Exercise has been shown to reduce risk and improve prognosis of several types of cancers. Irisin is a myokine linked to exercise and lean body mass, which is thought to favorably alter metabolism systemically, potentially providing benefit for metabolic disease (including cancer). We evaluated the effects of various concentrations of irisin (with and without posttranslational modifications) on malignant and non-malignant breast epithelial cell number, migration and viability. Irisin significantly decreased cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 26 publications
9
134
1
1
Order By: Relevance
“…Although speculative, this idea may be of particular importance in the context and development of pharmacological and therapeutic uses of irisin. These findings are similar to those recently generated by our group showing that irisin promotes caspase-dependent apoptosis of malignant breast epithelial, independent of NFκB activity [12]. Moreover, palmitate-induced NFκB activation (phospho-NFκB expression) of AML12 cells and/or primary hepatocytes was reduced by concurrent treatment with recombinant irisin [30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although speculative, this idea may be of particular importance in the context and development of pharmacological and therapeutic uses of irisin. These findings are similar to those recently generated by our group showing that irisin promotes caspase-dependent apoptosis of malignant breast epithelial, independent of NFκB activity [12]. Moreover, palmitate-induced NFκB activation (phospho-NFκB expression) of AML12 cells and/or primary hepatocytes was reduced by concurrent treatment with recombinant irisin [30].…”
Section: Discussionsupporting
confidence: 90%
“…Cells were grown to confluency prior to differentiation for normalization. Recombinant irisin was purchased from Cayman Chemical (Ann Arbor, MI) and recombinant IL6 and TNFα from R and D Systems (Minneapolis, MN) were diluted to various concentrations in culture media identified through pilot data (specifically PGC-1α expression) and through previous observations [5,12,21]. Differentiated myotubes were treated with various doses of each agent for 24 h. In order to investigate the potential rescuing effect of irisin on suppressed metabolism, we treated differentiated myotubes with various doses of simvastatin from Sigma (St. Lois, MO) determined through pilot data with and without irisin or DMSO control (final concentration of DMSO=0.1 % for all experiments using simvastatin) for 24 h.…”
Section: Cell Culturementioning
confidence: 99%
“…In a study, it has been shown that the irisin application does not affect the viability of endometrial (KLE and RL95-2), colon (HT29 and MCA38), thyroid (SW579 and BHP7) and esophagus (OE13 and OE33) cancer cells [20]. In another study, it has been reported that while the treatment of irisin to human malign breast epithelial cells (MCF-10a) does not change the cell viability, it causes a decrease in the amount of viable malign aggressive breast epithelial cells [36].…”
Section: Discussionmentioning
confidence: 96%
“…El año 2014, el estudio de Gannon y cols, los hallazgos sugieren que la Irisina tiene un efecto supresor en el nú-mero de células y características migratorias de las células malignas de cáncer de mama; así como también demostraron que es capaz de inducir apoptosis en dichas células (54).…”
Section: Irisina Y Trastornos Metabólicosunclassified